The Hexaco Personality Traits of Higher Achievers at the University Level - Jia, Ruofan; Bahoo, Rabia; Cai, Zhendong; Jahan, Musarrat (Frontiers in Psychology, 2022)
The current study attempted to explore the personality traits of higher achievers at the university level. The core objective of the current investigation was to illustrate the nature of personality traits of higher achievers’ students. To study this phenomenon, a quantitative research approach was used. The students were chosen by using a purposive sampling technique and included 758 high achievers enrolled in various programs at Chinese universities. Based on the Hexaco model of personality, a questionnaire was used to gather information from respondents as a research tool to examine the personality traits of position holders after an extensive review of the relevant literature. Tool validity was determined by following the face, content, construct (convergent, and discriminant validity) validation process. The current investigation concluded that honesty, emotionality, and openness to experience were very high among higher achievers’ students. Only honesty in female higher achievers’ students was significantly high than male, remaining factors “extraversion, agreeableness, conscientiousness and openness to experience” were significantly high among male higher achievers’ students. Moreover, higher achievers of science group students were more extraversion, agreeableness and conscientiousness than arts group students. However higher achievers in hostels were more emotional and agreeableness than day scholars. Overall step-wise regression analysis, agreeableness and extraversion factor has significant influence on higher achievers.